Moderate alcohol consumption is associated with better endothelial function: a cross sectional study - Suzuki, Keiko (BioMed Central, 2009)
BACKGROUND: Moderate alcohol consumption is protective against coronary artery disease. Endothelial dysfunction contributes to atherosclerosis and the pathogenesis of cardiovascular disease. The effects of alcohol consumption on endothelial function may be relevant to these cardiovascular outcomes, but very few studies have examined the effect of alcohol consumption on endothelial function assessed by flow-mediated dilation (FMD) of the brachial artery in humans. METHODS: In the population-based Northern Manhattan Study (NOMAS), we performed a cross-sectional analysis of lifetime alcohol intake and brachial artery FMD during reactive hyperemia using high-resolution B-mode ultrasound images among 884 stroke-free participants (mean age 66.8 years, women 56.6%, Hispanic 67.4%, black 17.4%, and white 15.2%). RESULTS: The mean brachial FMD was 5.7% and the median was 5.5%. Compared to non-drinkers, those who drank >1 drink/month to 2 drinks/day were more likely to have FMD above the median FMD (5.5%) (unadjusted OR 1.7, 95% CI 1.2–2.4, p = 0.005). In multivariate analysis, the relationship between moderate alcohol consumption and FMD remained significant after adjusting for multiple traditional cardiovascular risk factors, including sex, race-ethnicity, body mass index, diabetes mellitus, coronary artery disease, Framingham risk score, medication use (adjusted OR 1.8, 95%CI 1.1–3.0, p = 0.03). No beneficial effect on FMD was seen for those who drank more than 2 drinks/day. CONCLUSION: In conclusion, consumption of up to 2 alcoholic beverages per day was independently associated with better FMD compared to no alcohol consumption in this multiethnic population. This effect on FMD may represent an important mechanism in explaining the protective effect of alcohol intake on cardiovascular disease.